ISLAMIC BOARDING SCHOOL MANAGEMENT IN IMPROVING TEACHER COMPETENCE AT MODERN BOARDING SCHOOL AL - MUSYADDAD KLATEN - Alfin Yunianto; M Rikza Chamami (PT. Jurnal Center Indonesia Publisher, 2025)
Pesantren management is a series of systems, rules, and governance of educational institutions structured within the framework of values in pesantren. Activities or functions in pesantren management include planning, organizing, directing, and supervising. Teachers or ustad have a central role in pesantren. Ustad also acts as a mentor and role model for the students. There are four competencies that must be possessed by a teacher, namely pedagogical, social, professional, and personality competencies. In this study focuses on the teacher's personality competence, where ustad is expected to have attitudes and behaviors that can be emulated by the students. Pondok Modern Al-Musyaddad is a modern cottage that emphasizes Arabic and English in its daily conversation, and uses a curriculum using the term KMI (Kulliyatul Mu'alimin Al-Islamiyah) in its learning. This study aims to analyze how management at Pondok Modern Al-Musyaddad and how pesantren management in improving teacher competence at Pondok Modern Al-Musyaddad. The method used is qualitative research with data collection techniques through observation, interviews, and documentation. The results showed that pesantren management at Pondok Modern Al-Musyaddad Klaten has been running well in improving the personality competence of teachers/ustad.